The Influence of Digital Marketing and Promotion on Visiting Interest in Shangri-La Hotel Jakarta - Gagih Pradini; Akristi Eni; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
Hotels are an alternative accommodation that is quite preferred by immigrants, so the price aspect greatly affects the interest and interest of immigrants to stay at the hotel. Shangri-La Hotels Jakarta is a 5-star hotel located in sudirman area, Central Jakarta. The purpose of this research is to find out the influence of Digital Marketing and Promotion on Visiting Interests at Shangri-La Hotel Jakarta. Sampling in this study using purposive sampling techniques. The data in this study was collected through primary data, namely by distributing questionnaires to 98 respondents. Data analysis in this research uses testing techniques that are in SPSS 23. The results of the research prove that the digital marketing and promotion variables, together produce data that affects the interest in visiting at Shangri-La Hotel Jakarta.